Infection of Children with Covid-19 Virus - Sura I.A.Jabuk, Shaymaa O. H. Al-Mamoori, Rasha Kadhim Mahdi, Zahraa M. Altaee, Anmar M. K. Al-Maamori, Noor S. Naji (Scientific Trends, 2023)
Coronavirus can infected children of all ages (Covid-19). But most children suffer from symptoms are generally not as severe as adults, and some may have no symptoms at all. Children's immune systems may also be interacting with the virus differently from adult immune systems. Children are also less likely to experience long-term health issues like diabetes, high blood pressure, or heart disease.
Keywords: children, Covid-19, Corornavirus